Scopus weighted CiteScore: A better alternative to plain CiteScore - Kumar, Atul; Gawande, Amol; Kale, Shailendrakumar; Agarwal, Akash; Brar, Vinaydeep; Raibagkar, Shirish (Iberoamerican Journal of Science Measurement and Communication, 2025)
Objective. CiteScore has become a widely used tool for assessing journal performance in recent years. This paper aims to show the limitations of the plain CiteScore and propose a better alternative: the weighted CiteScore, which captures the percentage of publications cited and improves journal ranking. Design/Methodology/Approach. Using an exploratory research methodology, we show the limitation of a plain CiteScore, calculated by dividing the past four years' citations by publications in the past four years. We demonstrate how a plain CiteScore can convey misleading results about the overall quality of a journal based on one or a few high-performing publications. Using the Wilcoxon signed-rank test, we prove that the journal Citescore ranking changed significantly using a weighted CiteScore method. Results/Discussion. The analysis shows how a single open-access paper’s citation can significantly swing the overall ranks and percentiles in a specific domain due to plain CiteScore. Weighted CiteScore better represents the journal's performance, considering the number of publications cited. Conclusions. Results of ranking journals based on plain CiteScore can be misleading. Our hypothetical and empirical analysis shows the need for a weighted CiteScore methodology. There has to be a level playing field by factoring in the percentage of publication citations. Originality/value. The paper makes a novel contribution by suggesting an accurate and fair performance metric. It will be of significant value to libraries and researchers when assessing the quality of a publication.